Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found